Growth of Pepper Cuttings (Piper ningrum L.) at various type of Plant growth regulator - K. Kasriana; Marlina Mustafa; Yolanda Fitria Syahri (Universitas Sembilanbelas November Kolaka, 2017)
Pepper is an important crop in Indonesia because it is one of the country's foreign exchange sources because it is one of the export commodities. The availability of good plant materials will support increased production. Provision of growth regulators in vegetative propagation is very influential on the propagation of pepper plants. The purpose of this study was to determine the most effective combination of growth regulators for pepper cutting. This study was conducted using a randomized block design consisting of eight treatments namely Control (P1), metallic 2 mL L-1 water (P2), mastafol 2 mL (p3), Atonik 2 mL (P4), metallic 1 mL + Mastafol 1 mL (P5), metallic 1 mL + atonic 1 mL (P6), mastafol 1 mL + atonic 1 mL (P7), metallic 0.66 mL + Mastafol 0.66 mL + Atonic 0.66 mL (P8). Setek is grown on soil media: fuel husk: manure (2: 1: 1). The results showed that the best Plant growth regulator combination treatment for the growth of pepper cuttings was P7 (mastafol 1 mL L-1 water + atonic 1 mL L-1 water), which can be seen in the parameters of the number of roots, root length, root volume and number of shoots. The treatment of Plant growth regulator given did not significantly affect the character of leaf growth